2017
DOI: 10.1155/2017/2519814
|View full text |Cite
|
Sign up to set email alerts
|

Granulosis Rubra Nasi Response to Topical Tacrolimus

Abstract: Granulosis Rubra Nasi (GRN) is a rare disorder of the eccrine glands. It is clinically characterized by hyperhidrosis of the central part of the face, most commonly on the tip of the nose, followed by appearance of diffuse erythema over the nose, cheeks, chin, and upper lip. It is commonly seen in childhood but it can present in adults. Here we report a case of GRN in an adult patient with very unusual histopathological presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…GRN is a rare focal form of hyperhidrosis that usually manifest in childhood and disappears during puberty. Primary hyperhidrosis leading to sweat retention localized to central region of face is the principal reason 4 . GRN worsens in summer and can resolve during winter 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GRN is a rare focal form of hyperhidrosis that usually manifest in childhood and disappears during puberty. Primary hyperhidrosis leading to sweat retention localized to central region of face is the principal reason 4 . GRN worsens in summer and can resolve during winter 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, lesions may reoccur despite above‐mentioned therapy. GRN has a good prognosis with minimal complication and self‐resolves in most cases 4 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Te tip of the nose is usually red/ violet, cold, and not infltrated. Tis condition is usually asymptomatic except for mild pruritus [7]. Heid et al had reported an association with rhinorrhea [6].…”
Section: Discussionmentioning
confidence: 99%
“…Granulosis rubra nasi -It is a disease of eccrine sweat glands, first described by Jadassohn in 1901 as "nasi hyperhidrotic erythematosa micropapules dermatosis infantum." 6 Usually, it starts during childhood as localized hyperhidrosis on the central face, typically affecting the tip, alae and dorsum of the nose. This is followed by secondary changes like blanchable erythema, papulo-vesicles and pustules.…”
Section: Pityriasis Lichenoides -It Was First Reported Bymentioning
confidence: 99%